2009
DOI: 10.1002/cmdc.200800421
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Neurotensin Analogues Exhibit Sub‐picomolar Anticonvulsant Potency in a Pharmacoresistant Model of Epilepsy

Abstract: Neurotensin (NT) is an endogenous neuropeptide involved in a variety of central and peripheral neuromodulatory effects. Here we show effects of site-specific glycosylation on the in vitro and in vivo pharmacological properties of this neuropeptide. NT analogs containing O-linked disaccharides (β-melibiose and α-TF antigen) or β-lactose unit linked via a PEG3-spacer were designed and chemically synthesized using Fmoc chemistry. For the latter analog, Fmoc-Glu-(β-Lac-PEG3-amide) was prepared. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Building blocks such as N ε -acyl-Lys and LAA can be chemically synthesized and directly coupled on resin by the Fmoc solid phase peptide synthesis (SPPS) method [18,[159][160][161]. S-Acylated cysteine is not recommended due to possible aminolysis by the α -amino group [162].…”
Section: Chemical Synthesis Methodsmentioning
confidence: 99%
“…Building blocks such as N ε -acyl-Lys and LAA can be chemically synthesized and directly coupled on resin by the Fmoc solid phase peptide synthesis (SPPS) method [18,[159][160][161]. S-Acylated cysteine is not recommended due to possible aminolysis by the α -amino group [162].…”
Section: Chemical Synthesis Methodsmentioning
confidence: 99%
“…The encoded protein is likely involved in the termination of the neurotensinergic signal in the central nervous system and in the gastrointestinal tract. In particular, in specific brain regions examined (amygdala, corpus callosum, and caudate nucleus), it showed strong expression, with moderate expression in cerebellum, hippocampus, substantia nigra, and thalamus [Lee et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Several endogenous neuropeptides, such as NPY (YPSKP‐DNPGEDAPAEDMARYYSALRHYINLITRQRY‐NH 2 ), NT (ZLY‐ENKPRRPYIL), and GAL (GWTLNSAGYLLGPHAVGNHRSFS DKNGLTS‐NH 2 ), possess both antiepileptic and antinociceptive properties mediated by their respective receptors in the CNS1–3. These neuropeptides show promise as potential first‐in‐class therapeutics for the treatment of epilepsy and/or pain.…”
Section: Introductionmentioning
confidence: 99%
“…This 13‐residue peptide has been widely studied for its antinociceptive properties, shown to be mediated through two receptor subtypes, NTR‐1 and NTR‐219, 20. More recently, Lee and coworkers demonstrated the ability of NT and its glycosylated analogs to suppress epileptic seizures in the brain with remarkable potency (for NT, ED 50 = 0.001 nmol in the 6 Hz mouse model of epilepsy, intracerebroventricular injection)2. SAR studies have revealed that the C ‐terminal portion of the peptide, NT (8–13), is sufficient for receptor activation21, 22.…”
Section: Introductionmentioning
confidence: 99%